Design and development of Nrf2 modulators for cancer chemoprevention and therapy: a review - Sova M; Saso L (Dove Medical Press, 2018)
Matej Sova,1 Luciano Saso2 1Faculty of Pharmacy, University of Ljubljana, Ljubljana, Slovenia; 2Department of Physiology and Pharmacology “Vittorio Erspamer”, Sapienza University, Rome, Italy Abstract: A major cell defense mechanism against oxidative and xenobiotic stress is mediated by the Nrf2/Keap1 signaling pathway. The Nrf2/Keap1 pathway regulates gene expression of many cytoprotective and detoxifying enzymes, thus playing a pivotal role in maintaining redox cellular homeostasis. Many diseases including cancer have been closely related to impaired Nrf2 activity. Targeting Nrf2 and modulating its activity represents a novel modern strategy for cancer chemoprevention and therapy. In this review, different design strategies used for the development of Nrf2 modulators are described in detail. Moreover, the main focus is on important and recently developed Nrf2 activators and inhibitors, their in vitro and in vivo studies, and their potential use as chemopreventive agents and/or cancer therapeutics. Keywords: Nrf2, oxidative stress, signaling pathway, cytoprotective, chemopreventive agents, cancer therapeutics